Hibridisasi ikan koi (Cyprinus rubrofuscus) dan ikan kaviat (Barbonymus schwanenfeldii) dengan menggunakan pemijahan buatan - Nasita, Abian Surya; Rostika, Rita; Priowirjanto, Gatot Hari; Davinci, Leonardo (Jurnal Sumberdaya Akuatik Indopasifik, 2025)
Fish hybridization is the process of crossing two different fish species to produce offspring that have characteristics of both parents. The main purpose of hybridization is usually to combine superior traits from both species, such as faster growth, disease resistance, or improved meat quality. The experimental design used in this study was a completely randomized design (CRD) with 2 treatments and each treatment consisted of 3 replicates. The treatments were as follows: P1 = Koi X Koi Fish Hatchery (control), P2 = Koi X Kaviat Fish Hatchery. The results showed that the pH value in borehole water quality was 7.89 with Kohaku broodstock producing fecundity of 640 eggs, obtained an average Fertilization Rate (FR) of 17.29% resulting from the average of each egg sample calculation. The highest number of fertilized eggs was found in the PIU1 treatment which was 1470 eggs and the average Hatching Rate (HR) was 49.35%. The conclusion of this study is that hybridization between Koi and Kaviat fish can produce good potential performance based on water quality that can be maintained well with test parameters seen from fecundity, FR, HR, Length Growth, and good Survival Rate (SR).  Superior fecundity and quality in the hybridization process between koi and caviat fish can occur well if several environmental factors such as temperature and pH are still on an optimal scale.